Non-transfusion dependent HbE/βO-thalassemia as the results of co-existent SEA-αO thalassemia, Hb Constant Spring, and XmnI-Gγ site: Thai family studies - Tatu, Thanusak; Tondee, Wachirawit; Khamtong, Pornchai; Tangphan, Lamplimas; Jaitiang, Jidapa (Journal of Associated Medical Sciences, 2023)
Background: Four university students of northern Thai descent were found to be HbE/βO-thalassemia. However, they all had a mild form of this disease, categorized as Non-Transfusion Dependent Thalassemia. Objectives: To analyze involvement of types of β-globin mutations, α-thalassemia, and XmnI-Gγ site in mild clinical symptoms observed in four Thai non-transfusion dependent HbE/βO-thalassemia cases. Materials and methods: EDTA blood samples were collected from the patients and their family members after signing the informed consent. Automated complete blood count with blood smear examination, hemoglobin typing, molecular analysis for α and β-globin mutations, β-globin gene haplotypes, and XmnI-Gγ site were performed on all blood samples. In addition, nucleotide sequencing of β-globin gene and globin chain separation were performed for patient#3 and their parents. Results: The first three patients had hemoglobin levels ranging 8.5-11.2 g/dL, while the fourth patient had hemoglobin level of 6.7 g/dL. The first and fourth patients were compound heterozygote for βE (HBB:c.79G>A) and β17 (HBB:c.52A>T) alleles with typical hemoglobin pattern of EF. The second patient was compound heterozygote for βE and β41/42 (HBB:c.126_129delCTTT) alleles also with typical hemoglobin pattern of EF. The third patient was compound heterozygote of βE and βIVS1-1(HBB:c.92+1G>T), however, with atypical hemoglobin pattern of EE. Family analysis found co-inheritance of Hb Constant Spring (HBA2:c.427T>C) and the XmnI-Gγ site (T at rs7482144) in the first two patients, of SEA-αO thalassemia (NG_000006.1:g.26264_45564del19301) and XmnI-Gγ site in the third patient, and of only XmnI-Gγ site in the fourth patient. Conclusion: These family studies proved the fact that co-existence of SEA-αO thalassemia and Hb Constant Spring in HbE/βO-thalassemia could lead to mild clinical severity. Minimal effect of XmnI-Gγ site on clinical symptoms of this disease was emphasized. This information should be useful in prenatal diagnosis of HbE/β-thalassemia.